Impact of Sharia Stock Prices: A Study on Inflation, Exchange Rate, BI Rate, and Money Supply - Subagio, Sidiq; Rahayu, Sovi Ismawati (Research of Islamic Economics, 2024)
This study aims to examine the effect of inflation, exchange rate, BI Rate, and the amount of money in circulation on Islamic stocks in companies listed on the Jakarta Islamic Index (JII). This study uses a sample of changes in the inflation rate, changes in the exchange rate, changes in the BI rate, changes in the money supply, and Islamic stock prices. This study uses secondary data, namely reports of changes in index obtained from the official website of the Indonesian Stock Exchange and the website of the Central Statistics Agency. With the results obtained in this study, inflation has a significant negative effect on Sharia Stock Prices, Exchange Rates have a significant negative effect on Sharia Stock Prices, amount of money in circulation has a significant positive effect on the price of Sharia shares. Inflation, Exchange Rate, BI Rate, and Money Supply have a simultaneous effect on Sharia Stock Prices in Companies Listed in the Jakarta Islamic Index. Managerial implications, especially for investment managers and fund managers in the Islamic capital market. Knowing the influence of inflation, exchange rates, BI interest rates, and money supply on Islamic stock prices allows managers to make better and more strategic investment decisions.